In Search of Social Democracy Responses to Crisis and Modernisation - Callaghan, John; Fishman, Nina; Jackson, Ben; McIvor, Martin (Manchester University Press, 2009)
Focusing on the social democratic heartland of Western Europe, In search of social democracy gives the first detailed assessment of how the new social democratic revisionism has fared in government. The book begins by considering the causes of the end of social democracy's golden age and the magnitude of the challenges faced by social democratic parties after the 1970s. It then examines detailed case studies of how particular social democratic parties responded to this changed political terrain. Finally, it contributes to a broader conversation about the future of social democracy by considering ways in which the political thought of 'third way' social democracy might be radicalised for the twenty-first century. The contributors offer a variety of perspectives, but are united by the conviction that the themes addressed in this book are crucial to determining the feasibility of more egalitarian and democratic social outcomes than have been possible in the era of neo-liberalism.